2009
DOI: 10.1590/s0100-204x2009001000021
|View full text |Cite
|
Sign up to set email alerts
|

Características testiculares de touros imunizados com vacina anti-hormônio liberador do hormônio luteinizante

Abstract: Resumo -O objetivo deste trabalho foi avaliar a ação imunoesterilizadora de uma vacina anti-hormônio liberador de hormônio luteinizante (LHRH), composta por ovalbumina-LHRH-7 e tiorredoxina-LHRH-7, em touros mestiços Nelore. Vinte e seis touros, com dois anos de idade, foram distribuídos aleatoriamente em dois grupos de 13 animais. No grupo I, os animais receberam uma dose e dois reforços da vacina nos dias 0, 141, e 287 do experimento. No grupo II, os animais não receberam nenhum tratamento (controle). Para a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
7
1
2
Order By: Relevance
“…The performance characteristics of the immunocastrated bulls in this study are contrary to the results of Zanella et al (2009), who compared non-castrated and immunocastrated bulls and concluded that non-castrated Nelore bulls, with breeding and finishing in a grazing regime, had a higher weight gain but a diminished carcass finish compared with the immunocastrated animals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The performance characteristics of the immunocastrated bulls in this study are contrary to the results of Zanella et al (2009), who compared non-castrated and immunocastrated bulls and concluded that non-castrated Nelore bulls, with breeding and finishing in a grazing regime, had a higher weight gain but a diminished carcass finish compared with the immunocastrated animals.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, an alternative is immunocastration using a vaccine that stimulates the production of antibodies against the synthesis of gonadotropins anti-gonadotropin-releasing hormone (GnRH) antibodies, which inhibit the liberation of luteinising hormone (LH) and follicle-stimulating hormone (FSH) by the pituitary gland and thus suppress testicular function in males, with a subsequent decrease in the concentration of blood testosterone (ZANELLA et al, 2009).Another alternative to surgical castration is veterinary homeopathy, which is indicated for both the healing and prevention of diseases, the control of stress and the improvement of performance and feed conversion, as well as for controlling the sexual behaviour of sodomy (SOUZA, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, castration further improves carcass quality (i.e. reduced taint, increased marbling, and greater meat yield) and animal welfare of swine, goats, and sheep (Dunshea et al 2001, Zanella et al 2009, Moraes et al 2010, Trujillo et al 2011, Abbá et al 2012, Lanferdini et al 2012, Zamaratskaia and Rasmussen 2015. Male castration also aids efforts to control population of domestic dogs, cats, and donkeys (Almeida and Silva 2010, Theubet et al 2010, Abu-Ahmed 2015, Silva et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Em animais zebuínos de dois anos de idade criados à campo na região do Mato Grosso do Sul, também houve diminuição no perímetro escrotal de animais imunocastrados, estes com 22 cm, enquanto animais não castrados 35,6 cm [14]. Ao abate, os testículos dos animais imunocastrados do presente experimento apresentaram também menor comprimento e largura em comparação aos animais não castrados e, consequentemente, menor tamanho total, representados por largura versus comprimento.…”
Section: Discussionunclassified
“…Em trabalhos que utilizaram três doses da vacina anti-hormônio liberador de hormônio luteinizante (LHRH) em bovinos Nelore de dois anos de idade, a degeneração testicular associada a descamação do epitélio seminífero também foi visualizada histologicamente nos animais imunocastrados, com proporção de 85% com ausência de espermatogênese e 15% com redução parcial, podendo ser explicada como consequência de uma provável retomada funcional das células de Sertoli após a aplicação do último reforço vacinal ou por inibição parcial da espermatogênese [14]. Em bovinos com 6 a 8 meses de idade, a diminuição no diâmetro dos túbulos seminíferos também foi significativa nos animais imunocastrados em relação aos animais controle [13], semelhante à redução visualizada no presente estudo.…”
Section: Discussionunclassified